The effect of aerobic exercise and garlic supplement administration on insulin, glucose, and sleep pattern of prediabetic obese women with sleep disorders - M Rezaei; KH Irandoost; M Taheri; SH Mahdavi (فصلنامه ابن سینا)
Background: Physiological and behavioral disorders such as diabetes and sleep disorders have been considered as vital issues for middle-aged adults; therefore, the purpose of this study was to investigate the effect of aerobic exercise and garlic intake on insulin and glucose of prediabetic obese women with sleep disorders. Materials and methods: 32 non-active prediabetic obese women with mean age of 44.33±5.59 were enrolled to the study and randomly divided into two groups of training with or without garlic supplement intake. The serum glucose and insulin levels, as well as sleep pattern of individuals were compered before and after the course. Results: the results suggested that fasting glucose levels were improved significantly in both training groups (respectively, t=7.79, p=0.001 and t=6.85, p=0.001), while Insulin was improved only in supplement-training group (t=7.79, p=0.001). Comparing the two groups showed that glucose levels were significantly different with a preference for supplement training group (p=0.001), while no significant difference was found for insulin. Quality of sleep and its parameters were also improved significantly after intervention (p≤0.05) except sleep efficacy in training group which it improvement was not significant. Conclusion: Training along with garlic supplement has an effective role in regulation of blood glucose and insulin in prediabetic obese patients and mere aerobic training will also result in glucose regulation.